Research on 1/6 g Environment Simulation System Based on Magnetic Levitation Suspension - Lei Ma; Ruihan Xu; Hailong Song; Songkai Liu (IEEE Access, 2024)
The 1/6g environment simulation system is essential in scientific research, exploration, and future space development. The system is technically demanding and must accurately simulate a low-gravity environment while ensuring the reliability and precision of the experiment, which involves complex machinery and control systems that are technically challenging. This paper proposes a new simulation experiment method that combines the traditional hanging low-gravity simulation method and magnetic levitation technology.Realization of the design of the magnetic levitation suspended low gravity simulation system. The magnetically levitated overhead crane, which counteracts 5/6 of the lunar rover’s gravity, is the most important component of the entire test system. The article first designs the principle scheme of the magnetically levitated hanging active following a low gravity simulation system, which reduces the influence of the bulky wheel slip structure of the existing equipment on the experiment and improves the system’s anti-interference ability. Secondly, the article establishes the dynamics model of the magnetic suspension crane tracking system, analyzes and derives the relationship between the force, the magnetic suspension air gap and the voltage, and lays a theoretical foundation for the smooth operation of the precise control system. Finally, based on the cross-coupling control strategy, the magnetic suspension crane following control system is designed and the cross-coupling control system model is established.